THE INFLUENCE OF LEARNING MODEL AND SCHOOL ORIGIN ON PSYCHOMOTOR OUTCOMES ISLAMIC FAITH AND MORALITY - Polem, Muhammad; Cahya, Afrilia Dwi; Akbarjono, Ali; Kariadinata, Rahayu; Malik, Adam (Nurul Jadid University, Paiton Probolinggo, East Java, 2023)
The aim of this research is to examine existence or absence of the influence and interaction between the learning models (PBL, PjBL, Conventional) and students' school origins in determining psychomotor learning outcomes in the subject of Islamic Faith and Morality. The method used in this research is a quantitative approach with a Quasi-Experimental Design using the Nonequivalent Control Group Design type. The research results indicate that the implementation of the PBL, PjBL, and Conventional learning models in determining psychomotor learning outcomes in Islamic Faith and Morality does not significantly differ from each other. This is reinforced by the Post Hoc Model Learning table. PBL vs. PjBL with an Asymp. Sig. value of 0.260 > 0.05. PBL vs. Conventional with an Asymp. Sig. value of 0.083 > 0.05. PjBL vs. Conventional with an Asymp. Sig. value of 1.000 > 0.05. In conclusion, there are differences in students' psychomotor learning outcomes based on the learning model with an Asymp. Sig. value of 0.001 < 0.05. There are no differences in students' psychomotor learning outcomes based on school origins with an Asymp. Sig. value of 0.470 > 0.05, and there’s an interaction between the learning model and school origins as evidenced by the Asymp.Sig. value of 0.007 < 0,05. So the implications in this research illustrate that students' psychomotor learning outcomes in the Akidah Akhlak subject are more dominantly influenced by the learning model applied in the classroom rather than the student's school origin.